Comparison the Effects of Massage with Olive Oil and Sweet Almonds Oil on Prevention of Pressure Ulcer in Hospitalized Patients in ICU - Shokoh Varaei; Leila Shirbeygi; Leila Farahani; Zainab Eslami Hasan Abadi; Morteza Shamsizadeh (Hamadan University of Medical Sciences, 2019)
Introduction: Pressure ulcer is a complication from which many patients suffer. Preventing this matter is one of the duties of nurses. The purpose of this study was to determine the effect of massage of olive oil with sweet almonds on prevention of pressure ulcer in patients hospitalized in ICU. Methods: This study is a double-blind randomized clinical trial that was performed on 90 patients admitted to ICU Hospital in Maybod city, Yazd, Iran. Patients were selected by purposeful sampling and random blocked method in enrolled in two groups of test and one control group. The patients of the test groups received a massage in the areas exposed to risk of pressure ulcer for a week once a day with 3-1 mL of olive oil or sweet almonds. Also these two groups received the usual skin care including a change in position every two hours and a wavy mattress and control group received just the usual care of the skin. Data was collected using a demographic questionnaire and a checklist for potential areas with the risk of pressure ulcer using Braden's scale. Data was analyzed by Chi-square test, Fisher's exact test and variance analysis test in SPSS 16. Results: There was no statistically significant difference between the groups in terms of demographic variables. The results showed that the incidence of pressure ulcers in the experimental groups was lower than the control group and in the olive oil massage group was lower than the sweet almond oil massage group (P<0.05). Conclusion: The results showed that olive Oil and sweet almond massage is effective in preventing pressure ulcer. A similar study to this study should be done using other herbal products such as Aloe Vera gel to prevent Pressure ulcer.